2009
DOI: 10.1007/s10553-009-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of oxygenates

Abstract: The mechanism of the action of oxygenates is discussed from the standpoint of redox reactions. It is shown that the action of oxygenates on the process of combustion of hydrocarbons is associated with oxidation of the latter in steps. The reason for the increase in octane number upon addition of oxygenates may be different rate of overcoming conformational differences under conditions close to the critical temperature of the hydrocarbon at the pre-ignition combustion stage. The influence of propylene oxide on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since PO is produced in large industrial scales and could be easily transported, it was proposed as an oxygenated additive to transportation fuels , to reduce soot content in the exhaust of diesel engines. Recent study has shown that there is no evidence that typical environmental or occupational exposures to PO constitute a health risk for humans .…”
Section: Introductionmentioning
confidence: 99%
“…Since PO is produced in large industrial scales and could be easily transported, it was proposed as an oxygenated additive to transportation fuels , to reduce soot content in the exhaust of diesel engines. Recent study has shown that there is no evidence that typical environmental or occupational exposures to PO constitute a health risk for humans .…”
Section: Introductionmentioning
confidence: 99%
“…Propylene oxide (PO) has been examined as another oxygenate [2][3][4]. The mechanism of action of oxygenates, including propylene oxide, was proposed in [5]. The physicochemical and performance characteristics of composite fuels must be investigated for incorporating oxygenate compositions with propylene oxide.…”
mentioning
confidence: 99%